Basic density of wood from seven species and three clones of eucalyptus before and during shiitake cultivation - Andrade, Meire Cristina Nogueira de; Minhoni, Marli Teixeira de Almeida; Sansigoto, Cláudio Angeli; Cunha Zied, Diego (Acta Scientiarum - Agronomy, 2009)
Basic density of the wood and bark of seven eucalyptus species (E. saligna, E.grandis, E. urophylla, E. camaldulensis, E. citriodora, E. panicnlata and E. pellita) and three eucalyptus clones (E. grandis x E. urophylla hybrids) were evaluated before and during the cultivation of shiitake (Lentinula edodes) strains LE-95/01 and LE-96/18 in logs. Each shiitake strain was inoculated into 9 logs of each type of eucalyptus with length of 1 m and diameter of 9 to 14 cm. Thus, the experimental design was totally randomized, with 20 treatments and 9 repetitions, with each repetition corresponding to one log. The logs were kept in a greenhouse, under the temperature of 25 ± 5°C and relative air humidity between 60-80 %, during 12 months. To determine basic density, newly cut disks and barks wedges of eucalyptus (without the inoculation of L. edodes strains) and disks wedges removed from logs inoculated with L. edodes strains after 8 and 12 months of incubation were analyzed. It was verified that wood basic density decreased in all types of eucalyptus along the cultivation cycle.
Densidade básica da madeira de sete espécies e três clones de eucalipto antes e durante o cultivo de shiitake
Keywords: Basidiomycota; Eucalyptus; Eucalyptus Camaldulensis; Eucalyptus Grandis; Eucalyptus Pellita; Eucalyptus Saligna; Eucalyptus Urophylla; Lentinula Edodes